The distribution of marine debris and microplastic in Tidung Kecil Island, Jakarta Bay and Sembilang National Park, Palembang. Issue 1 (May 2021) - Sulistiowati,; Zamani, N P; Ismet, M S
Abstract: Plastic waste is one of the marine debris that has negative impacts on the marine environment, such as the death of biota and disturbing the beauty of nature. Plastics can degrade into microplastics. Microplastics in the marine environment can be found in waters and sediments, so they can enter the biota through the food chain. The research aims to examine the distribution of marine debris and microplastics on small islands (Tidung Kecil, Jakarta Bay) and the mainland (Sembilang National Park, South Sumatra). The total marine debris on Tidung Kecil Island (4.04 kg/m 2 ) was greater than that of Sembilang National Plants (0.71 kg/m 2 ). The average abundance of microplastics in the larger size area is greater than in small islands. This is because the substrate is predominantly clayey and muddy with a relatively calm environment, while on small islands the substrate is sand with a dynamic environment. The amount of marine debris found did not correlate with the abundance of microplastics.